Model Pengaturan Pembagian Harta Bersama pada Proses Perceraian yang Bersumber dari Royalti Hak Cipta - Kirana Apsari; Ni Ketut Supasti Dharmawan (Jurnal Ilmiah Kebijakan Hukum, 2025)
Songs and music created by musicians have economic value that can support their households, as does the royalty income generated from copyright. During marriage, conflicts and disputes often arise, sometimes leading to divorce. In divorce proceedings, copyright royalties are not exempt from claims made by either the husband or wife. This study aims to elaborate on the status of royalties earned from copyright as part of marital property in the context of divorce, examine how these royalties are divided as joint assets, and provide legal certainty regarding royalty distribution. The research employs a normative legal method with a statutory approach, a conceptual approach, and a legal analysis approach. The findings indicate that royalties can be considered joint property. In the event of a divorce, they may be divided equally between the spouses, or the court may determine a different percentage based on the judge’s considerations of fairness. For instance, in Decision No. 1622/Pdt.G/2023/PA.JB, the court ruled that half (½) of 50% of the net income should be allocated to the former spouse. Additionally, the division of royalties can be based on a prenuptial agreement between the spouses. Therefore, LMKN plays a crucial role in preventing disputes over royalty amounts by implementing Article 14, paragraph (2) of Government Regulation No. 56/2021, ensuring clear royalty distribution based on reported data on song and/or music usage.